Digital Tools and Language Learning Strategies: Enhancing Students’ Engagement and Achievement in Graduate Studies - Vivit Rosmayanti (Darussalam English Journal (DEJ), 2025)
This study explores the role of digital tools and language learning strategies in engagement and achievement at the graduate level. This was achieved through a mixed-methods strategy that included a sampling survey with Likert scales as well as in-depth coding of qualitative data. The survey was distributed through the platform and consisted of 15 open-ended questions measuring cognitive, emotional, and behavioral types of engagement on a scale of 1 to 5. The descriptive-analytical methods and qualitative coding were used to measure engagement and student experiences. Emotion engagement was found to be the strongest, while cognitive engagement was high as well but behavioral engagement was relatively lower, indicating participants’ struggle to keep up the consistency in studying. Interactive learning, real-life practice, and even motivational collaboration were used as qualitative analysis reveals while technical difficulties and poor attendance were provided. The results call for some degree of caution in the application of such digital tools that must be incorporated strategically. Future research should find ways to improve behavioral engagement and overcome technological hurdles to improve the overall effectiveness of the digital learning experience.